Общие направления эволюции брюшка браконид (Hymenoptera, Braconidae) - Тобиас, В.И.; Дударенко, Г.П. (Вестник зоологии, 1974)
Formation of the abdomen test from the first three tergites is one of the main trends (or tendencies) in evolution of Braconidae family. In all the big subfamilies of the Braconidae family there are both generalized and specialized <testaceous» forms. The investigations carried out permitted establishing that the abdomen evolution in many subfamilies of the investigated family proceeds simultaneously and independently and results in formation of the abdomen similar in its external structure in different not closely-related groups of Braconidae.